A novel study on amyloid β peptide 40, 42 and 40/42 ratio in Saudi autistics - Al- Ayadhi, Laila Y (BioMed Central, 2012)
OBJECTIVES: We examined whether plasma concentrations of amyloid beta (Aβ) as protein derivatives play a central role in the etiology of autistic features. DESIGN AND METHODS: Concentrations of human Aβ (1-42), Aβ (1-40), and Aβ (40/42) in the plasma of 52 autistic children (aged 3-16 years) and 36 age-matched control subjects were determined by using the ELISA technique and were compared. RESULTS: Compared to control subjects, autistic children exhibited significantly lower concentrations of both Aβ (1-40) and Aβ (1-42) and lower Aβ (40/42) concentration ratio. Receiver operating characteristics curve (ROC) analysis showed that these measurements of Aβ peptides showed high specificity and sensitivity in distinguishing autistic children from control subjects. CONCLUSIONS: Lower concentrations of Aβ (1-42) and Aβ (1-40) were attributed to loss of Aβ equilibrium between the brain and blood, an imbalance that may lead to failure to draw Aβ from the brain and/or impairment of β- and γ- secretase's concentration or kinetics as enzymes involving in Aβ production.